Studi Deskriptif tentang Sanitasi Tempat Wisata Desa Terindah Pariangan di Kabupaten Tanah Datar - Sugriarta, Evino; Oktafiani, Monica (CV. CENDIKIA JENIUS INDONESIA, 2023)
The Most Beautiful Village of Pariangan is one of the interesting tourist attractions to visit in Tanah Datar Regency. The problem found in the most beautiful village of Pariangan is that the environmental conditions are less clean. The aim of this research is to find out the description of the sanitary conditions of the most beautiful tourist attraction in Pariangan Village. This research is descriptive in nature. The object of this research is the condition of the physical environment and the condition of sanitation facilities at the Teindah Pariangan Village tourist attraction. The observed data is processed manually and analyzed then the results are compared with the regulations of the Directorate General of P2PM and PLP No. 47 of 1999 and presented in table and narrative form. The results of research from Terindah Pariangan Village are that the environmental conditions do not meet the requirements with a score of 60%, the sanitary conditions for providing clean water meet the requirements with a score of 70%, the sanitary conditions of public toilets do not meet the requirements with a score of 60%, the sanitary conditions for waste water disposal do not meet the requirements requirements with a score of 20%, sanitary conditions for waste disposal do not meet the requirements with a score of 40%, sanitary conditions of places of worship meet the requirements with a score of 90%. It is hoped that the management should provide cleaning staff, provide public faucets, and order traders who sell around tourist attractions to treat the waste water they produce.